Strategic Planning and Structural Inertia in Azerbaijan's Post-Oil Economy: An Evaluation of the 2016-2025 National Roadmap - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2025)
This paper provides an empirical assessment of Azerbaijan's Strategic Roadmap for the National Economy, adopted in 2016 with targets set through 2025. Drawing on official statistics and the author's own calculations, the study evaluates performance against four core objectives: (i) raising average annual real GDP growth above 3 percent; (ii) increasing the share of foreign direct investment (FDI) in non-oil GDP to 4 percent; (iii) boosting non-oil exports per capita from USD 170 to USD 450; and (iv) reducing the state budget's dependence on transfers from the State Oil Fund of Azerbaijan (SOFAZ) to 15 percent. The analysis shows that none of these targets have been met. Average annual GDP growth over 2016-2025 is estimated at 1.46 percent, well below the planned threshold. The share of FDI in non-oil GDP declined from 6.9 percent in 2016 to 0.7 percent in 2024, while per capita non-oil exports reached only about USD 330-more than 20 percent short of the 2025 target. At the same time, SOFAZ transfers still account for more than one-third of state budget revenues and are projected to remain structurally high. Labour-market indicators reveal additional fragility, with inflated job-creation figures, substantial job closures, and persistent reliance on public sector employment. The findings point to a systematic implementation gap between strategic planning and actual outcomes, rooted in structural and institutional constraints rather than exogenous shocks alone. The paper concludes that without significant reforms in governance, investment climate, and statistical transparency, Azerbaijan's strategic planning exercises will continue to underperform as instruments of genuine diversification and structural transformation.
Keywords: O21; 330; Azerbaijan; Strategic Roadmap; Economic Diversification; Foreign Direct Investment; Non-Oil Exports; SOFAZ; Fiscal Dependence; Labour Market; Implementation Gap; Policy Evaluation